Pelimpahan Kuota Haji bagi Jamaah yang Meninggal Dunia: Analisis Maqashid Syariah serta Implementasinya di Indonesia dalam Perspektif Sosiologi dan Antropologi - Mulyadi, Kiking; Mukhlas, Oyo Sunaryo; Saebani, Beni Ahmad (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The transfer of hajj quotas for deceased pilgrims is a legal and social issue that is relevant to the dynamics of the implementation of the hajj in Indonesia. This phenomenon arises as a consequence of the long waiting list for the departure of pilgrims, which causes many prospective pilgrims to die before having the opportunity to perform the worship. From the perspective of Islamic law, the hajj is personal (fard 'ain) and attached to individuals who have met the requirements of istitha'ah. However, in the context of state administration, the right to portion Hajj is seen as an administrative right that can be transferred to certain heirs in a regulatory manner. This study aims to examine the legal basis for the assignment of hajj quota based on the principles of sharia maqashid and review its implementation in the socio-anthropological context of the Indonesian Muslim community. The research method used is normative law with a conceptual and sociological approach, through the analysis of laws and regulations and developing social practices. The results of the study show that the transfer of the hajj quota does not contradict sharia principles as long as it brings benefits, guarantees justice, and avoids potential abuse. Socially, this policy reflects respect for the deceased's worship intentions, strengthens kinship values, and shows the adaptation of Islamic law in responding to the needs of contemporary Indonesian Muslim society.